Roles of microRNA-124 in traumatic brain injury: a comprehensive review - Wu, Panxing; He, Bao; Li, Xiaoliang; Zhang, Hongwei (Frontiers in Cellular Neuroscience, 2023)
Traumatic brain injury (TBI) is a prominent global cause of mortality due to the limited availability of effective prevention and treatment strategies for this disorder. An effective molecular biomarker may contribute to determining the prognosis and promoting the therapeutic efficiency of TBI. is the most abundantly expressed in the brain and exerts different biological effects in a variety of diseases by regulating pathological processes of apoptosis and proliferation. Recently, increasing evidence has demonstrated the association between miR-124 and TBI, but there is still a lack of relevant literature to summarize the current evidence on this topic.Based on this review, we found that miR-124 was involved as a regulatory factor in cell apoptosis and proliferation, and was also strongly related with the pathophysiological development of TBI. MiR-124 played an essential role in TBI by interacting with multiple biomolecules and signaling pathways, such as JNK, VAMP-3, Rela/ApoE, PDE4B/mTOR, MDK/TLR4/NF-κB, DAPK1/NR2B, JAK/STAT3, PI3K/AKT, Ras/MEK/Erk. The potential benefits of upregulating miR-124 in facilitating TBI recovery have been identified. The advancement of miRNA nanocarrier system technology presents an opportunity for miR-124 to emerge as a novel therapeutic target for TBI. However, the specific mechanisms underlying the role of miR-124 in TBI necessitate further investigation. Additionally, comprehensive large-scale studies are required to evaluate the clinical significance of miR-124 as a therapeutic target for TBI.